2022
DOI: 10.1039/d2sc00848c
|View full text |Cite
|
Sign up to set email alerts
|

Robust dicopper(i) μ-boryl complexes supported by a dinucleating naphthyridine-based ligand

Abstract: Copper boryl species have been widely invoked as reactive intermediates in Cu-catalysed C−H borylation reactions, but their isolation and study have been challenging. Use of the robust dinucleating ligand DPFN...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…On the other hand, reports on dinuclear 1,8-naphthyridine complexes, in which the metal atoms are in close proximity of each other, have shown that auxiliary ligands or substrates tend to bind in the center between the two metal centers. 25 , 31 , 35 , 37 41 It therefore reflects the reactivity of these complexes better to choose the center of the binding pocket, in the middle of the two metal atoms, as the origin of the sphere for V bur calculations ( Figure 2 ). The standard sphere diameter for mononuclear complexes is 3.5 Å; 42 however, for a dinuclear binding pocket, the sphere size should be larger to encompass both metals and their surroundings sufficiently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, reports on dinuclear 1,8-naphthyridine complexes, in which the metal atoms are in close proximity of each other, have shown that auxiliary ligands or substrates tend to bind in the center between the two metal centers. 25 , 31 , 35 , 37 41 It therefore reflects the reactivity of these complexes better to choose the center of the binding pocket, in the middle of the two metal atoms, as the origin of the sphere for V bur calculations ( Figure 2 ). The standard sphere diameter for mononuclear complexes is 3.5 Å; 42 however, for a dinuclear binding pocket, the sphere size should be larger to encompass both metals and their surroundings sufficiently.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are examples in the literature in which V bur calculations are applied to dinuclear complexes, the buried volume maps are only used for visualization of the accessible pocket, 29 , 30 or the sterics around a bridging ligand are evaluated. 31 However, to the best of our knowledge, the V bur and G- parameter methods have not been used to quantify the sterics of the combined dinuclear binding site. As these methods were developed for mononuclear complexes, it is unclear if they can be reliably expanded to complexes wherein two metals are present at varying distances.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, reports on dinuclear 1,8naphthyridine complexes in which the metal atoms are in close proximity of each other, have shown that auxiliary ligands or substrates tend to bind in the center between the two metal centers. [22,28,32,[34][35][36][37][38] It therefore reflects the reactivity of these complexes better to choose the center of the binding pocket, in the middle of the two metal atoms, as the origin of the sphere for Vbur calculations (Figure 2). The standard sphere diameter for mononuclear complexes is 3.5 Å, [39] however, for a dinuclear binding pocket the sphere size should be larger to encompass both metals and their surroundings sufficiently.…”
Section: Buried Volume Of Pnnp Ligandsmentioning
confidence: 99%
“…To aid the development of this type of complexes, reliable characterization of the sterics of these complexes would be beneficial. Although there are examples in literature in which Vbur calculations are applied to dinuclear complexes, the buried volume maps are only used for visualization of the accessible pocket [26,27] , or the sterics around a bridging ligand are evaluated [28] However, to the best of our knowledge the Vbur and G-parameter methods have not been used to quantify the sterics of the combined dinuclear binding site. As these methods were developed for mononuclear complexes, it is unclear if they can be reliably expanded to complexes wherein two metals are present at varying distances.…”
mentioning
confidence: 99%
“…Copper(I) boryls have seen particular interest owing to their exploitation under catalytically relevant conditions. [10] This interest has also resulted in the isolation and structural characterisation of an ever growing range of copper(I) boryls, [11][12][13] aided by the ease of their synthesis. With a few notable exceptions, [13][14][15] copper(I) boryl bonds are made via a CuÀ O/BÀ B σ-bond metathesis between a ligated copper alkoxide and a diborane.…”
Section: Introductionmentioning
confidence: 99%